2021
DOI: 10.1038/s42003-021-02710-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the breast cancer lipidome and its interaction with the tissue microbiota

Abstract: Breast cancer is the most diagnosed cancer amongst women worldwide. We have previously shown that there is a breast microbiota which differs between women who have breast cancer and those who are disease-free. To better understand the local biochemical perturbations occurring with disease and the potential contribution of the breast microbiome, lipid profiling was performed on non-tumor breast tissue collected from 19 healthy women and 42 with breast cancer. Here we identified unique lipid signatures between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 59 publications
1
17
0
Order By: Relevance
“…the antigens from Staphylococci) increase adiponectin secretion and decrease resistin secretion in vitro [29] . A recent study evaluated lipid signatures with chromatography and mass spectometry in association with the breast tissue microbiome in samples taken from clinically normal breast tissue from women with cancer or undergoing breast reduction [30] . The investigators found decreased ceramides, lipids with tumor suppressive antiproliferative effects, in tissues from women with breast cancer while in samples from the women without cancer there was increased relative abundance of bacteria genera with the capacity to synthesize these lipids including diacylglycerols, second messengers that drive activation, proliferation, migration, and effector function of both adaptive and innate immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…the antigens from Staphylococci) increase adiponectin secretion and decrease resistin secretion in vitro [29] . A recent study evaluated lipid signatures with chromatography and mass spectometry in association with the breast tissue microbiome in samples taken from clinically normal breast tissue from women with cancer or undergoing breast reduction [30] . The investigators found decreased ceramides, lipids with tumor suppressive antiproliferative effects, in tissues from women with breast cancer while in samples from the women without cancer there was increased relative abundance of bacteria genera with the capacity to synthesize these lipids including diacylglycerols, second messengers that drive activation, proliferation, migration, and effector function of both adaptive and innate immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] However, the relationship between endometrial bacteria and EC development is of greater concern than that between gut microbiota and EC development because tissue microbiota may directly affect tumor behavior. 20,21 About tissue microbiota, more enigmas wait to be urgently clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple microbial compartments undergo oncobiotic transformation during breast cancer, including breast tissue [55,56], milk ducts [57], the inherent microbiome of the breast carcinoma [54,[58][59][60][61][62][63][64][65][66][67][68][69][70][71][72], the distal gut [51,52,[73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89], and the urinary microbiome [54,90]. However, no differences in the microbiome of the nipple [57,69] and the oral microbiome [54] between healthy individuals and breast cancer patients have been detected.…”
Section: Oncobiosis In Breast Cancermentioning
confidence: 99%
“…Furthermore, the intricate supportive metabolic circuit between cancer cells and non-cancerous stroma cells can facilitate tumor growth and lead to worse clinical outcomes [103][104][105]113]. Giallourou and colleagues [71] showed that breast bacteria interfere with the biosynthesis of ceramide, cholesterol, oxidized cholesteryl esters, diacylglycerol, lysophosphatidylcholine, phosphatidylethanolamines, and phosphatidylcholines to modulate the lipid composition of tumors. Of note, cholesterol and lipid homeostasis also play a role [4,[114][115][116].…”
Section: Tumor Colonizationmentioning
confidence: 99%
See 1 more Smart Citation